Multiple stones in neobladder: Case report and literature review. Issue 4 (November 2019) - Tafuri, Alessandro; Porcaro, Antonio B; Ashrafi, Akbar N; Cerruto, Maria Angela; Amigoni, Nelia; Mariotto, Arianna; Sebben, Marco; Marcer, Anna; Bassi, Silvia; Medina, Luis G; Cacciamani, Giovanni E; Baccaglini, Willy; et al.
Introduction: Neobladder urolithiasis is a rare but important long-term complication of orthotopic urinary diversion. It may be asymptomatic and can be discovered as an incidental finding on a radiological investigation. However, when symptoms occur, they may include lower abdominal pain, dysuria, hematuria, and lower urinary tract symptoms. Case description: We report the case of a 63-year-old male patient with irritative lower urinary tract symptoms, lower abdominal fullness, urinary incontinence, fecaluria, and urinary loss from the left inguinal fold 12 years after a radical cystoprostatectomy with a orthotopic neobladder. Computed tomography scan and urethrocystography showed a distended pouch with multiple large stones, an enterovesical fistula, and neovesicocutaneous fistula. The fistulae were successfully managed conservatively with the placement of a Foley catheter. After 3 months, open cystolithotomy was performed and approximately 50 stones with dimensions varying from 5 mm to 5 cm, with a total weight of 890 g, were removed. After a 1-year follow-up, the patient did not report pain, urinary tract infections, or symptoms suggestive of fistula and imaging evaluation confirmed no recurrence of neobladder stones. Conclusion: Neobladder stones may present with various symptoms. Our patient had irritative lower urinary tract symptoms, lower abdominal fullness, urinary incontinence, fecaluria, and urinary loss from the left inguinal fold 12 years after a radical cystoprostatectomy with a orthotopic neobladder. Our experience demonstrates that open cystolithotomy is an effective intervention for the removal of large stones in neobladder.